Ultrasonic velocity and attenuation of low-carbon steel at high temperatures - Tai, Jan Lean; Sultan, Mohamed Thariq Hameed; Łukaszewicz, Andrzej; Shahar, Farah Syazwani; Tarasiuk, Wojciech; Napiórkowski, Jerzy (MDPI AG, 2023)
On-stream inspections are the most appropriate method for routine inspections during plant operation without undergoing production downtime. Ultrasonic inspection, one of the on-stream inspection methods, faces challenges when performed at high temperatures exceeding the recommended 52 °C. This study aims to determine the ultrasonic velocity and attenuation with known material grade, thickness, and temperatures by comparing theoretical calculation and experimentation, with temperatures ranging between 30 °C to 250 °C on low-carbon steel, covering most petrochemical equipment material and working conditions. The aim of the theoretical analysis was to obtain Young’s modulus, Poisson’s ratio, and longitudinal velocity at different temperatures. The experiments validated the theoretical results of ultrasonic change due to temperature increase. It was found that the difference between the experiments and theoretical calculation is 3% at maximum. The experimental data of velocity and decibel change from the temperature range provide a reference for the future when dealing with unknown materials information on site that requires a quick corrosion status determination.